FACTORS CONTROLLING DEVELOPMENT OF CHICK EMBRYO LIVER CELLS DURING ORGAN CULTURE - Benzo, Camillo A. (The Rockefeller University Press, 1971)
The 5 day chick embryo liver cell still lacks many of the ultrastructural features of the adult liver cell. During organ culture on rafts over Eagle's medium, it develops electron-opaque mitochondria with granules, biliary microvilli, and compact Golgi complexes containing what appears to be secretory material. Rough ER proliferates and free ribosomes become bound to membrane. Thus, the 5 day cell, exposed only to simple nutrients (glucose, amino acids, vitamins) develops the general appearance of the adult liver cell except for the continued absence of smooth ER and glycogen. The significance of this incomplete differentiation and the factors controlling development are discussed in the light of accompanying metabolic changes.